Addressing Students' Musical Interests in Non-Art Schools Through Playing the Song Kejar Mimpi - Juliko, Febi; Emridawati, Emridawati; Kustilo, Anton (Scoring: Journal of Film Music, 2023)
The song Chasing Dreams is a popular song created and popularized by Maudy Ayunda. This song was rearranged for the needs of non-arts schools to address some students' interest in music. In particular, schools that implement an independent learning curriculum do not have music education. Even though the independent curriculum provides space for students to express themselves freely. To address the school's needs and students' interests, this song will be played by seven students of SMKN 2 Padangpanjang from class 12. The instrument formats used to accommodate the students' interests include Keyboard, Cajon, Guitar, Bass Guitar, and Vocals. The method used to train non-arts students is action research through: lectures, demonstrations, exercises, experiments, and evaluations. The results of this research show that students' interest in this non-arts school is being able to demonstrate their abilities well in front of an audience at the graduation ceremony for PL students at SMKN 2 Padang Panjang.